2013
DOI: 10.1016/j.pec.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported use of collaborative goal setting and glycemic control among patients with diabetes

Abstract: Objective Little is known about how patient-clinician communication leads to better outcomes. Among patients with diabetes, we describe patient-reported use of collaborative goal setting and evaluate whether perceived competency and physician trust mediate the association between collaborative goal setting and glycemic control. Methods Data from a patient survey administered in 2008 to a cohort of insured patients aged 18+ years with diabetes who initiated oral mono-therapy between 2000–2005 were joined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 31 publications
0
53
0
1
Order By: Relevance
“…For example, SDM may improve patient satisfaction, which over time may lead to trust in the physician, followed by adherence to physician recommendations and ultimately improved health. (73) However, as of yet these relationships remain largely untested in the empirical literature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SDM may improve patient satisfaction, which over time may lead to trust in the physician, followed by adherence to physician recommendations and ultimately improved health. (73) However, as of yet these relationships remain largely untested in the empirical literature.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Indeed, in a study of 1065 patients with diabetes, Lafatta et al found that patient-reported use of more collaborative goal setting was associated with greater perceived self-management competency and increased level of trust in the physician ( p <0.05), which in turn were associated with improved glycemic control ( p <0.05). 44 Because high quality primary care is by definition longitudinal, patients and providers also have multiple opportunities over time to identify and address care priorities, and indeed these priorities may change over time as issues are addressed or circumstances change.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that patient reports of collaborative goal setting with healthcare providers are associated with increased perceived self-management competence1–3 and trust in their physician 14 Patient reports of engaging in collaborative goal setting have also been found to be associated with improved self-management behaviors and health outcomes, including improvements in Hemoglobin (Hb) A1c and blood pressure levels among patients with diabetes and hypertension 1…”
Section: Introductionmentioning
confidence: 99%